Communist parties revisited : sociocultural approaches to party rule in the Soviet Bloc, 1956-1991 - Bergien, Rüdiger; Gieseke, Jens (2018)
The ruling communist parties of the postwar Soviet Bloc possessed nearly unprecedented power to shape every level of society; perhaps in part because of this, they have been routinely depicted as monolithic, austere, and even opaque institutions. Communist Parties Revisited takes a markedly different approach, investigating everyday life within basic organizations to illuminate the inner workings of Eastern Bloc parties. Ranging across national and transnational contexts, the contributions assembled here reconstruct the rituals of party meetings, functionaries' informal practices, intra-party power struggles, and the social production of ideology to give a detailed account of state socialist policymaking on a micro-historical scale